Reticulibacter mediterranei gen. nov., sp. nov., within the new family Reticulibacteraceae fam. nov., and Ktedonospora formicarum gen. nov., sp. nov., Ktedonobacter robiniae sp. nov., Dictyobacter formicarum sp. nov. and Dictyobacter arantiisoli sp. nov., belonging to the class Ktedonobacteria. Issue 7 (23rd July 2021) - Yabe, Shuhei; Zheng, Yu; Wang, Chiung-mei; Sakai, Yasuteru; Abe, Keietsu; Yokota, Akira; Donadio, Stefano; Cavaletti, Linda; Monciardini, Paolo
Abstract : The aerobic, Gram-positive, mesophilic Ktedonobacteria strains, Uno17 T, SOSP1-1 T, 1-9 T, 1-30 T and 150040 T, formed mycelia of irregularly branched filaments, produced spores or sporangia, and numerous secondary metabolite biosynthetic gene clusters. The five strains grew at 15–40 °C (optimally at 30 °C) and pH 4.0–8.0 (optimally at pH 6.0–7.0), and had 7.21–12.67 Mb genomes with 49.7–53.7 mol% G+C content. They shared MK9(H2 ) as the major menaquinone and C16 : 1 -2OH and iso-C17 : 0 as the major cellular fatty acids. Phylogenetic and phylogenomic analyses showed that Uno17 T and SOSP1-9 T were most closely related to members of the genus Dictyobacter, with 94.43–96.21 % 16S rRNA gene similarities and 72.16–81.56% genomic average nucleotide identity. The strain most closely related to SOSP1-1 T and SOSP1-30 T was Ktedonobacter racemifer SOSP1-21 T, with 91.33 and 98.84 % 16S rRNA similarities, and 75.13 and 92.35% average nucleotide identities, respectively. Strain 150040 T formed a distinct clade within the order Ktedonobacterales, showing <90.47 % 16S rRNA gene similarity to known species in this order. Based on these results, we propose: strain 150040 T as Reticulibacter mediterranei gen. nov., sp. nov. (type strain 150 040 T =CGMCC 1.17052 T =BCRC 81202 T ) within the family Reticulibacteraceae fam. nov. in the order Ktedonobacterales ; strain SOSP1-1 T as Ktedonospora formicarum gen. nov., sp. nov. (type strain SOSP1-1 T =CGMCC 1.17205 T =BCRC 81203 T ) and strain SOSP1-30 T as Ktedonobacter robiniae sp. nov. (type strain SOSP1-30 T =CGMCC 1.17733 T =BCRC 81205 T ) within the family Ktedonobacteraceae ; strain Uno17 T as Dictyobacter arantiisoli sp. nov. (type strain Uno17 T =NBRC 113155 T =BCRC 81116 T ); and strain SOSP1-9 T as Dictyobacter formicarum sp. nov. (type strain SOSP1-9 T =CGMCC 1.17206 T =BCRC 81204 T ) within the family Dictyobacteraceae .